Sistem Mobile Application, Tracking Lokasi dan Estimasi Perjalanan Untuk Aplikasi Shuttle Bus Uk Petra Menggunakan Flutter dan Google Maps - Kevin Jonathan; Rolly Intan; Liliana Liliana (Jurnal Infra, 2022)
Petra Christian University (PCU) is a campus that is already growing rapidly becoming one of the popular university in Indonesia with thousands of students from Indonesia and outside Indonesia which is now located in Jalan Siwalankerto, exactly in number 121-131, Surabaya. Petra Christian University planned to launch Shuttle Bus with west Surabaya – Petra Christian University route to facilitate many of the students from west Surabaya to reach Petra Christian University and vice versa. But, this Shuttlebus needs a control system to manage the usage of this shuttle bus by students. This control system is divided in a few big features, which is registration, reservation, identification, tracking, and features related to rating and notification system. The research results showed that after the "Petra Shuttle Bus" application was designed, most of the passengers benefited from being able to make a reservation in advance along with accessing other important features such as viewing bus locations and rating related schedules for service improvement. In addition, the driver also feels benefited because with the current check-in system, this greatly facilitates the driver in the process of checking passengers’attendance who have made the reservations. Please note that this application is far from perfect and requires further improvement according to users’ feedback.